(untitled) (Revista de Ciências Agroveterinárias, 2005)
Prototheca sp. are algae with worldwide distribution, responsible for several diseases affecting both animals and man. In dairy cattle, they may cause mastitis. The present work describes the isolation of Prototheca sp. from milk samples obtained from three cows with chronic mastitis, in the region of Santa Catarina’s South Tableland. This is the first case described of mastitis caused by this agent in the region. Since Prototheca sp. is resistant to treatment with antibiotics, the best way of controlling the infection is to identify and eliminate infected animals.